ANALISIS KADAR KARBOHIDRAT, VITAMIN C, β-KAROTEN DAN BESI (Fe) PADA BUAH KERSEN (Muntingia calabura L) SECARA SPEKTROFOTOMETRI UV-VIS - Aldrik M Makahity; Yeanchon H Dulanlebit; Nazudin Nazudin (Molluca Journal of Chemistry Education (MJoCE), 2019)
Kersen fruit (Muntingia calabura L) is a fruit is existence found in everywhere, but generally nothing interest for consumtion almost people. In a kersen fruit contained many nutriet, aim from the study that is determine carbohydrate, vitamin C, β-caroten, and Fe levels in kersen fruit in the gain at Air Louw Village, Nusaniwe Sub-district, Ambon City. In this study analize sample using spectrophotometry UV-Vis with wavelength carbohydrate 486 nm, vitamin C 273 nm, β-caroten 473 nm and Fe 474 nm and using technique calibration curve. Analyze result is showed that carbohydrate level by 343,393 mg/100 g, vitamin C level by 178,96 mg/100 g, β-caroten level by 1,4831 mg/100 g, and Fe levels by 0,1025 mg/100 g. Based result study can conclusion if kersen fruit can be consumption as food material because having nutrient contet enough for human’s body